2020
DOI: 10.2220/biomedres.41.199
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-gut-brain axis: enteroendocrine cells and the enteric nervous system form an interface between the microbiota and the central nervous system

Abstract: The microbiota-gut-brain axis transmits bidirectional communication between the gut and the central nervous system and links the emotional and cognitive centers of the brain with peripheral gut functions. This communication occurs along the axis via local, paracrine, and endocrine mechanisms involving a variety of gut-derived peptide/amine produced by enteroendocrine cells. Neural networks, such as the enteric nervous system, and the central nervous system, including the autonomic nervous system, also transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 181 publications
(223 reference statements)
0
44
0
Order By: Relevance
“…It has been reported that intestinal microbiota disorders may promote the development and deterioration of the symptoms of irritable bowel syndrome, 24 and intestinal microbiota may affect the two-way communication between the enteric nervous system and central nervous system. 25 Previous studies have demonstrated that immune system activation and proinflammatory cytokines may indirectly affect skin. 26,27 This may be the possible mechanism underlying the indirect impact of intestinal skin microbiota on sensitive skin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that intestinal microbiota disorders may promote the development and deterioration of the symptoms of irritable bowel syndrome, 24 and intestinal microbiota may affect the two-way communication between the enteric nervous system and central nervous system. 25 Previous studies have demonstrated that immune system activation and proinflammatory cytokines may indirectly affect skin. 26,27 This may be the possible mechanism underlying the indirect impact of intestinal skin microbiota on sensitive skin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the administration of GABA-producing Lactobacillus brevis via soybean milk was revealed to be effective as an antidepressant in rats, such as fluoxetine [ 15 ]. Neuroactive compounds derived from gut microbiota metabolism act as potential mediators of communication between the gut microbiota and the host [ 16 ]. As evidence, some receptors and transporters critical for neuroactive compounds are found in enterocytes.…”
Section: Introductionmentioning
confidence: 99%
“…As evidence, some receptors and transporters critical for neuroactive compounds are found in enterocytes. For example, GABA transporters are present in the rat gastrointestinal tract [ 16 ]; dopamine receptors are widespread throughout the intestine [ 9 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect of calorie restriction and related microbiome shifts, thus far largely ignored, is the behavioral changes in humans undergoing CR. Physiological changes under CR have been shown to contribute to reduction of ageing rate and oxidative stress, lowering risk factors for cardiovascular diseases and alleviate obesity, and changing endocrinal functions that correlate to metabolism and physical health 8 . Yet, CR is shown to be able to modulate behavioral changes in both human and experimental models, in measurements that include both objective (for instance psychological well-being, cognitive functioning) and subjective (mood, subjective feelings of hunger etc., determined usually by questionnaires) criteria 9 .…”
Section: Introductionmentioning
confidence: 99%